Novel and reliable DACTylitis glObal Sonographic (DACTOS) score in psoriatic arthritis. Issue 8 (19th May 2020) - Zabotti, Alen; Sakellariou, Garifallia; Tinazzi, Ilaria; Idolazzi, Luca; Batticciotto, Alberto; Canzoni, Marco; Carrara, Greta; De Lucia, Orazio; Figus, Fabiana; Girolimetto, Nicolò; Macchioni, Pierluigi; McConnell, Rebecca; et al.
Abstract : Objectives: Dactylitis is one of the most typical features of psoriatic arthritis (PsA), with a high lifetime prevalence and inclusion in PsA clinical indices. Musculoskeletal ultrasonography (Msk-US) can readily detect inflammatory involvement of finger anatomical structures particular to dactylitis and monitor therapeutic effects. In this study, we aim to identify the characteristic lesions in PsA dactylitis of the hands, assess the reliability of Msk-US in scoring those lesions and develop a DACTylitis glObal Sonographic (DACTOS) score. Methods: After a systematic literature review on the use of Msk-US in PsA dactylitis, 12 rheumatologists participated in a three-round Delphi procedure and consensus meeting to agree on the sonographic elementary lesions characterising dactylitis and on the composition of a global sonographic score. Then, a web-based and a patient-based intra-rater and inter-rater reliability exercise was performed to assess those lesions included in the score. Results: DACTOS score was obtained by summing the scores of each lesion selected in the Delphi survey: subcutaneous soft tissue oedema, flexor tenosynovitis, peritendon extensor inflammation and synovitis. The DACTOS score ranges from 0 to 25. In the reliability exercises, we obtained moderate-to-excellent agreement for the sonographic lesions included in the score. Conclusions: The novel DACTOS score is a reliable measure to interpret the multiple characteristic sonographic features of dactylitis. The DACTOS score provides a useful global analysis of dactylitis of the hand and can represent a support to clinical diagnosis as well as a useful tool for the management and research in patients with PsA with dactylitis.